2019
DOI: 10.1017/s0963548319000026
|View full text |Cite
|
Sign up to set email alerts
|

Separation Choosability and Dense Bipartite Induced Subgraphs

Abstract: We study a restricted form of list colouring, for which every pair of lists that correspond to adjacent vertices may not share more than one colour. The optimal list size such that a proper list colouring is always possible given this restriction, we call separation choosability. We show for bipartite graphs that separation choosability increases with (the logarithm of) the minimum degree. This strengthens results of Molloy and Thron and, partially, of Alon. One attempt to drop the bipartiteness assumption pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…As two other pieces of evidence for Conjecture 6.2, we note that [2] showed that a triangle-free, ddegenerate graph may have χ(G) as large as d; the graph G which achieves this indeed has χ f (G) d log d . Finally, we note that [6] has found other applications of Conjecture 6.2, which would cleanly show certain other bounds regarding induced bipartite graphs. Slightly weaker versions of these bounds have been found by other more laborious methods.…”
Section: Conjectured Tight Boundsmentioning
confidence: 54%
See 1 more Smart Citation
“…As two other pieces of evidence for Conjecture 6.2, we note that [2] showed that a triangle-free, ddegenerate graph may have χ(G) as large as d; the graph G which achieves this indeed has χ f (G) d log d . Finally, we note that [6] has found other applications of Conjecture 6.2, which would cleanly show certain other bounds regarding induced bipartite graphs. Slightly weaker versions of these bounds have been found by other more laborious methods.…”
Section: Conjectured Tight Boundsmentioning
confidence: 54%
“…We want to show that χ(G) ≤ f (n, t); thus, it suffices to show that s √ n + 6 1/3 ys 3t 2/3 ≥ 1 (6) Substituting in the value for s, simple algebraic manipulations show that this is equivalent to showing:…”
Section: Proofmentioning
confidence: 99%
“…In this subsection we prove that Conjecture 1.1 holds for graphs with minimum degree at least n Ω (1) , which also proves the lower bound in Theorem 1.3 (iii). The following lemma appeared as [16,Theorem 3.4], and is a corollary of Johansson's theorem [22] for colouring triangle-free graphs and a connection between the fractional chromatic number and dense bipartite induced subgraphs (see [16,Theorem 3.1] and a discussion in Section 6).…”
Section: Graphs With Polynomially-large Minimum Degreementioning
confidence: 99%
“…In addition to maximising the number of edges, it is also very natural to study induced bipartite subgraphs of large minimum degree. This more local approach was taken recently by Esperet, Kang and Thomassé in [16], where they made a number of intriguing conjectures. Conjecture 1.1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation